Basics of the Development of Microwave Intensification of Upstream on the Example of Escherichia coli - D. B. Kuznetsov; A. Yu. Mironov; V. A. Neschislyaev; I. L. Volkhin; A. M. Korolyuk; E. V. Orlova; A. D. Shilina (Разработка и регистрация лекарственных средств)
Introduction. E. coli strains are the main microorganisms used for the production of a number of important biopharmaceutical products. There are no natural sources of microwave radiation on Earth, as it is absorbed by the upper atmosphere. No one doubts the importance of studying the biological effect of microwave radiation. The number of publications devoted to this problem is growing every year, and new ideas for the use of microwaves in drug production technology are emerging.Aim. Reveal the main effects of microwave irradiation and develop a technology for microwave intensification of E. coli culture growth.Materials and methods. This study presents the results of atomic force microscopy, refractometry, NMR relaxometry, turbidimetry, and lumimetry, demonstrating the possibility of microwave intensification of the cultivation process.Results and discussion. It was found that microwave irradiation leads to changes in the mobility of protons and the adsorption of water molecules on biopolymers and cells. These are the main links in the mechanism of "non-thermal" microwave action. A single microwave irradiation, depending on a number of parameters, can decrease or increase the growth of biomass. Studies of the bioluminescence of the E. coli strain with the lux-operon have shown that the optimal processing conditions do not negatively affect the luciferase production and metabolic activity of cells. Conclusion. The intensification procedure using microwave radiation can be considered a promising method and can provide new ideas for various applications in biotechnology.